INTERNALISASI BUDAYA SIPAKATAU, SIPAKAINGE, SIPAKALEBBI DAN PAMMALI DALAM KEPATUHAN PAJAK UMKM KOTA MAKASSAR - Syahriana Ramadani; Bahar Sinring; Tenriwaru Tenriwaru (Fakultas Ekonomi dan Bisnis Universitas Atma Jaya Makassar, 2021)
This study aims to determine the role of the philosophy of sipakatau, sipakainge, sipakalebbi and pammali in improving SMEs tax compliance in Makassar City. This study uses a qualitative method with an ethnographic approach with interpretive paradigm by Max Weber and the informants used in this study are SMEs and tax officials in Makassar City. Data methods used are data reduction, triangulation, data presentation, data verification, conclusions, and the final meaning of the study. The results of this study stated that internalizing the culture of sipakatau, sipakainge, sipakalebbi and pammali would be able to improve the SMEs tax compliance of in Makassar City.